California Elected Women's Association for Education and Research Board Meeting Agenda (1977)
This document is the agenda for the July 22, 1977 CEWAER Board Meeting, outlining key organizational business and upcoming events. Topics include reports on regional development (notably a San Diego meeting), planning for CEWAER's participation in the California League of Cities and National League of Cities meetings, preparation for a meeting with the Governor, budget projections for 1977–78, workshops at the National Women's Political Caucus, and the May 1978 annual conference. The agenda reflects CEWAER's focus on policy engagement, networking, and organizational growth.